THE IMPACT OF ARTIFICIAL INTELLIGENCE IN FOREIGN LANGUAGE LEARNING USING LEARNING MANAGEMENT SYSTEMS: A SYSTEMATIC LITERATURE REVIEW - Oke Oluwafemi Ayotunde; Dashty Ismil Jamil; Nadire Cavus (Інформаційні технології і засоби навчання, 2023)
Among numerous foreign languages, the English language is considered one of the major languages of the world. It has become a door opener for many people in their different fields and have led to advancements in career areas as it plays a major role in boosting confidence, improving connection, communication, and so on. It also gives people the opportunity for self-expression on a global standard level. Although the learning process of a foreign language can sometimes be difficult for both learners and teachers in terms of the various aspects of language learning, which includes; reading, writing, speaking, and listening skills. The methodology in this study implemented a systematic literature review using four popular scientific databases for searching relevant records for the purpose of the research. The results from searching the databases were integrated into the PRISMA flow diagram for the identification and extraction of high quality records that is relevant to the effects artificial intelligence has in the process of foreign language learning via the use of learning management system as the platform and medium for learning and teaching English as a foreign language. The systematic review research covers a span of 10 years, from 2011 to 2021. The most important finding in this systematic literature review is that the emergence of AI technology is helpful to both students and teachers in the learning of English as a foreign language using a learning management system as it improves and increases speaking, writing, reading, and listening skills processes and provides an easy, interesting, and personalized learning experience. The benefit of the study to shareholders; students and teachers, is to guide teachers on which AI tools to use and how they can be integrated or used into learning management systems to increase students’ reading, writing, speaking, and listening skills in teaching and learning foreign languages, especially the English language.